Конкурентное и кооперативное поведение клеток в микроспорогенезе покрытосеменных - Кравец, Е.А.; Плоховская, С.Г.; Горюнова, И.И.; Сидорчук, Ю.В.; Мурсалимов, С.Р.; Дейнеко, Е.В.; Емец, А.И.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2016)
Aim. A comparative cytological analysis of intra- and intertissue cytomictic interactions in early microsporogenesis of mono- and dicotyledonous plants was performed using two cellular systems: microsporocytes and tapetum. Methods. Light and fluorescent microscopy. Results.There have been found complex forms of collective «social» cell behavior between tapetal cells and microsporocytes. The altruistic behavior prevails among microsporocytes, while competitive relationships dominate between microsporocytes and tapetal cells (only monocots). Polyploid tapetum nuclei and syncytia as powerful acceptors are able to compete with microsporocytes and guide the chromatin translocation to their favor. Conclusions. Intertissue interactions reflect likely the intensification of competition for area in anther between the tapetum and microsporocytes. The absence of intertissue interactions in dicots probably reflects a better balance of differentiation of anther somatic and generative tissues comparatively to monocots. Keywords: cytomixis, microsporogenesis, tapetum, «social» cell behavior, cell competition.